1998
DOI: 10.1021/cm9807079
|View full text |Cite
|
Sign up to set email alerts
|

SAXS and USAXS Investigation on Nanometer-Scaled Precursors in Organic-Mediated Zeolite Crystallization from Gelating Systems

Abstract: The formation of precursor particles in the crystallization of zeolites from gelating systems has been studied using X-ray scattering at small angles. The crystallization of Si-MFI using trimethylene-bis(N-hexyl, N-methyl-piperidinium) as the structure-directing agent shows the formation of two categories of precursors: gel particles and nanometer-scaled primary units. The size of the primary units for the crystallization of Si-MFI is found to be 2.8 nm both for gelating and nongelating systems using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 20 publications
(26 reference statements)
6
83
2
Order By: Relevance
“…These PDDFs for fresh dC6-silica and TPA-silica sols are consistent with PN morphologies that diverge from the monodisperse spheres, and this diversion is greater in the dC6-silica sols as compared to the TPA-silica sols. The present results differ from previous reports [26,[35][36][37] that concluded that PN sizes are specific to the zeolite framework formed and suggested a common PN size and shape regardless of which MFI-producing SDA was employed.…”
Section: Silicalite-1 Crystallization In Dc6-silica Solscontrasting
confidence: 99%
“…These PDDFs for fresh dC6-silica and TPA-silica sols are consistent with PN morphologies that diverge from the monodisperse spheres, and this diversion is greater in the dC6-silica sols as compared to the TPA-silica sols. The present results differ from previous reports [26,[35][36][37] that concluded that PN sizes are specific to the zeolite framework formed and suggested a common PN size and shape regardless of which MFI-producing SDA was employed.…”
Section: Silicalite-1 Crystallization In Dc6-silica Solscontrasting
confidence: 99%
“…Various approaches were chosen to investigate the nucleation of zeolites. There is general agreement that for clear solution synthesis the initial formation process involves the hydrolysis of alkoxysilanes which is followed by condensation-polymerization and eventually formation of discrete particles of less than five nanometers [96,97].…”
Section: Mechanisms Of Zeolite Nucleationmentioning
confidence: 87%
“…Returning to Figure 2 (from point 2 to 3), a few hours after heating these TEOS/TPAOH solutions to~90 8C, clear evidence of growing crystals is observed by SAXS, [9,26,27] calorimetry [28] and other techniques. [29] Upon nucleation, silica in solution starts to be depleted by the growing crystals and we start to move from point 2 to point 3.…”
Section: Wwwchemeurjorgmentioning
confidence: 87%